2019
DOI: 10.5194/acp-19-12515-2019
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation and viscosity within secondary organic aerosol generated from diesel fuel vapors

Abstract: Abstract. Information on liquid–liquid phase separation (LLPS) and viscosity (or diffusion) within secondary organic aerosol (SOA) is needed to improve predictions of particle size, mass, reactivity, and cloud nucleating properties in the atmosphere. Here we report on LLPS and viscosities within SOA generated by the photooxidation of diesel fuel vapors. Diesel fuel contains a wide range of volatile organic compounds, and SOA generated by the photooxidation of diesel fuel vapors may be a good proxy for SOA from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 129 publications
(197 reference statements)
1
39
0
Order By: Relevance
“…[66][67][68] The existence of LLPS in a purely organic SOA particle below 90% RH has only been observed previously for SOA generated by the photooxidation of diesel fuel vapors. 62 The presence of LLPS down to as low as 20% RH for sp-SOA, suggests that LLPS could be more common in organic SOA systems than previously thought.…”
Section: Llpsmentioning
confidence: 92%
See 2 more Smart Citations
“…[66][67][68] The existence of LLPS in a purely organic SOA particle below 90% RH has only been observed previously for SOA generated by the photooxidation of diesel fuel vapors. 62 The presence of LLPS down to as low as 20% RH for sp-SOA, suggests that LLPS could be more common in organic SOA systems than previously thought.…”
Section: Llpsmentioning
confidence: 92%
“…The procedure for LLPS has been described by Song et al (2019). 62 In short, the hydrophobic glass slides containing the SOA samples were placed in a RH and temperature-controlled ow cell. The RH was monitored using a chilled-mirror dew point hygrometer (General Eastern M4/E4 dew point monitor, Canada).…”
Section: Liquid-liquid Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…2, even though an overlapped C=O (from COOH) peak at 1660-1680 cm −1 appeared during the dehydration process, and the water peak became undetectable, as shown in the Raman spectra at RHs of 45 % and 3 %, suggesting an amorphous and solid state as well as the presence of an activation barrier or diffusional resistance to homogeneous nucleation required for the crystallization of MBTCA droplets as efflorescence is a kinetically controlled process (Martin, 2000;Freedman, 2017). Previous studies reported that αpinene SOAs were very likely to exist as a highly viscous semisolid or even glassy state at low humidity (Saukko et al, 2012;Renbaum-Wolff et al, 2013;Berkemeier et al, 2014;Dette et al, 2014;Kidd et al, 2014;Song et al, 2016;Lessmeier et al, 2018). In addition, many organic substances, such as carboxylic acids, carbohydrates, and proteins, tend to form amorphous rather than crystalline phases upon the drying of aqueous-solution droplets (Mikhailov et al, 2009).…”
Section: Hygroscopic Behavior Of Pure Mbtca Particlesmentioning
confidence: 92%
“…fine aerosol mass that exists as liquid, amorphous solid, semi-solid, and phase-separated aerosol particles (Jang et al, 2002;Hallquist et al, 2009;Jimenez et al, 2009;Virtanen et al, 2010;Koop et al, 2011;Bateman et al, 2015b;Shrivastava et al, 2015;Bernard et al, 2016;Pajunoja et al, 2016;Freedman, 2017;Shrivastava et al, 2017;Kim et al, 2018;Srivastava et al, 2018;Liu et al, 2019;Slade et al, 2019;Song et al, 2019;Wu et al, 2019a). These aerosols are of critical importance because of their ability to scatter and absorb solar radiation directly, to affect the number of CCN (cloud condensation nuclei) through the formation of new particles and the growth of preexisting particles, and further impact the climate and human health (Haywood and Boucher, 2000;Topping et al, 2013;Poschl and Shiraiwa, 2015;Reid et al, 2018;Marsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%